Measuring home environments across cultures: Invariance of the HOME scale across eight international sites from the MAL-ED study. (October 2017) - Jones, Paul C.; Pendergast, Laura L.; Schaefer, Barbara A.; Rasheed, Muneera; Svensen, Erling; Scharf, Rebecca; Shrestha, Rita; Maphula, Angelina; Roshan, Reeba; Rasmussen, Zeba; Seidman, Jessica C.; Murray-Kolb, Laura E.; et al.
Abstract: The home environment provides the context for much of a child's early development. Examples of important aspects of the home environment include safety, cleanliness, and opportunities for cognitive stimulation. This study sought to examine the psychometric properties of an adapted form of the Home Observation for the Measurement of the Environment (HOME; Caldwell & Bradley, 1984, 2003) across the eight international sites of the MAL-ED project (Dhaka, Bangladesh; Vellore, India; Bhakatapur, Nepal; Naushahro Feroze, Pakistan; Fortaleza, Brazil; Loreto, Peru; Venda, South Africa; Haydom, Tanzania), to identify a factor structure that fit the data at all sites, and to derive a subset of items that could be used to examine home environmental characteristics across sites. A three-factor structure (i.e., Emotional and Verbal Responsivity; Clean and Safe Environment; Child Cleanliness) was identified, and partial measurement equivalence/invariance across sites was supported. Overall, these findings lend support for the use of portions of this abbreviated and adapted version of the HOME for use among heterogeneous, cross-cultural groups in low- and middle-income nations.